2016
DOI: 10.1177/1470320316668737
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of angiotensinogen downregulates aquaporin 1 expression via modulation of Nrf2–HO-1 pathway in renal proximal tubular cells of transgenic mice

Abstract: Introduction:We aimed to examine the regulation of aquaporin 1 expression in an angiotensinogen transgenic mouse model, focusing on underlying mechanisms.Methods:Male transgenic mice overexpressing rat angiotensinogen in their renal proximal tubular cells (RPTCs) and rat immortalised RPTCs stably transfected with rat angiotensinogen cDNA were used.Results:Angiotensinogen-transgenic mice developed hypertension and nephropathy, changes that were either partially or completely attenuated by treatment with losarta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Chang et al. (2016) found that drugs affecting the renin–angiotensin system may modulate Nrf2/HO‐1 pathway which may have a serious effect on the oxidant/antioxidant balance in the cells. Also, Qi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al. (2016) found that drugs affecting the renin–angiotensin system may modulate Nrf2/HO‐1 pathway which may have a serious effect on the oxidant/antioxidant balance in the cells. Also, Qi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Aquaporin1 is the major water channel in renal proximal tubule and loop of Henle that is responsible for reabsorbing 80% of glomerular filtrate [75, 76]. It has been reported that renal and cardiac AQP1 expressions were downregulated in conditions such as renal fibrosis in mice [77] and HS-induced HPN [78].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the downregulation of AQP1 in both SHRs and WKY rats could be interpreted as a compensatory mechanism to prevent larger water reabsorption in the proximal tubule and the consequent expansion of extracellular fluid volume [27]. It has been claimed that in SHRs, the AQP1 expression in kidney [32, 75] and brain [75, 80] to be upregulated. However, the HS diet in the present study showed downregulation of both mRNA and protein levels of AQP1 (Fig 5A and 7A).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have documented that BDMC induces apoptosis by regulating HO-1 protein expression in activated HSCs [19]. In the present study, we tested whether cotreatment with BDMC and D 2 O can modulate the AQP11-dependent inhibition of cell proliferation effectively [28]. Our data revealed that BDMC coadministered with D 2 O markedly decreased cell proliferation by downregulating some cellular proteins including HO-1 and AQP11 and by inducing p53 (Figure 3).…”
Section: Discussionmentioning
confidence: 72%